Saneamento básico e salubridade ambiental em cidades do litoral do estado da Paraíba - Costa, Samara Gonçalves Fernandes (2017)
The lack of efficient planning in the urbanization process resulted in a deficit in meeting the growing population demand for basic sanitation services. This absence makes the environment unhealthy and directly affects the collective health and the environment. This problem has the greatest impact on the coastal cities, which have a high tourist potential due to their natural beauty such as the Paraíba coast. One way of evaluating the supply of these infrastructures is the use of tools that measure environmental quality as environmental indicators, as they provide information managers to act in a preventive and corrective manner. This study analyzed components of urban sanitation southern coast of Paraíba, comprising the cities in direct contact with the Atlantic Ocean (Cabedelo, Conde, João Pessoa and Pitimbu). Three basic sanitation services were characterized in their urban areas, assessing the infrastructure of the water supply system, sanitary sewage and solid waste as well as the environmental plans and actions that are being developed in the cities. The methodology used was the use of the Environmental Salubrity Indicator (ISA) calculated from data obtained in the National System of Basic Sanitation. It is concluded that the sanitation situation demonstrated by the ISA is of concern throughout the study area and there is no management that integrates the coastal aspect of existing public policies. The cities presented shortcomings in the provision of the service and in the offered quality. Providing this lack is essential to ensure a good quality of life and the preservation of the environment.